Learning with multimedia - More promise than practice? - Wiemeyer, J. (International Journal of Computer Science in Sport, 2003)
In the year 2000, the web-based education commission of the US government published a report on the power of the internet for learning (Kerrey & Isakson, 2000). The subtitle of this report is `Moving from promise to practice`. The report contains a strong call for action, i.e., the strong need for governmental engagement in order to support internet education. In this contribution, research findings are summarized in order to give a review concerning the question whether the promises of multimedia learning have been fulfilled. Furthermore, a model is proposed for developing multimedia systems for learning in a systematic way.